2014
DOI: 10.1021/ie500391b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Reactor Material Composition on Coke Formation during Ethane Steam Cracking

Abstract: An experimental study of the coking tendency of nine different materials was carried out in a quartz electrobalance setup with a jet stirred reactor (JSR) under industrially relevant ethane steam cracking conditions: T material = 1159 K, P tot = 0.1 MPa, χ ethane = 73%, dilution δ = 0.33 kg H2O /kg HC . A strong influence of the composition of the materials on the coking rate as a function of time on-stream was observed. The initial coking rate varied from 5SEM and EDX analyses of coked and uncoked coupons rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
150
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(160 citation statements)
references
References 54 publications
9
150
1
Order By: Relevance
“…It can be observed that for cycle 3, the coking rate reaches an asymptotic value of approximately 2 2 1 4 10 kg m s       . A similar tendency was observed 17 for the coking of an aluminium alloy during the decomposition of naphtha at 1098K. The decline in the coking rate as a function of time for the three cycles may be explained by the fact that the contact surface (and thus the catalytic surface) between the material and the n-dodecane reduces as the coke builds up in the thickness e 1 of the porous material.…”
Section: B Comparison Of Two Models: Linear and Exponentialsupporting
confidence: 71%
“…It can be observed that for cycle 3, the coking rate reaches an asymptotic value of approximately 2 2 1 4 10 kg m s       . A similar tendency was observed 17 for the coking of an aluminium alloy during the decomposition of naphtha at 1098K. The decline in the coking rate as a function of time for the three cycles may be explained by the fact that the contact surface (and thus the catalytic surface) between the material and the n-dodecane reduces as the coke builds up in the thickness e 1 of the porous material.…”
Section: B Comparison Of Two Models: Linear and Exponentialsupporting
confidence: 71%
“…Numerous investigations have been conducted to reduce coke formation, including altering the inner surface compositions on the inner surface of the coils, adding compounds, and increasing steam dilution ratio of feedstock …”
Section: Introductionmentioning
confidence: 99%
“…Over time, coke forms on the inner surface of the pyrolysis coils, especially in the radiant section where temperatures are highest, due to undesirable side reactions. Coke formation has a deleterious influence on the energy efficiency and economic viability of ethylene production processes . The coke layer on the coil surface reduces heat transfer to the process gas inside the coils due to low thermal conductivity of the coke layer.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting higher furnace temperature increases coil surface temperatures, which may reach or exceed the maximum permissible value imposed by the metallurgy of the coil . Note that coke formation is also associated with the formation of local hot spots that can damage furnace coils . Furthermore, the coke layer on the inside of the coils reduces the cross sectional area, which increases pressure drop through the coils if a constant ethylene production rate is maintained .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation